2021
DOI: 10.7759/cureus.17425
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Knowledge of Medical Students Towards Healthcare for Lesbian, Gay, Bisexual, and Transgender Seniors: Impact of a Case-Based Discussion With Facilitators From the Community

Abstract: Background: Lesbian, gay, bisexual, and transgender (LGBT) seniors are generally a medically underserved population that faces unique healthcare challenges. When compared to younger patients, LGBT seniors are at a greater risk for social isolation and have higher rates of smoking, disability, physical and mental distress, and lack of access to healthcare services. They are often reluctant to discuss their sexual orientations and gender identities with healthcare providers due to fear of discrimination and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Other facilitators were commonly identified at the audience level about which most authors referred to the advantage of students’/residents’ pre-existing awareness, knowledge, positive attitudes, interest, perceived significance, prior professional and/or lived experience that was a foundation for further learning on the topic of transgender health (Berenson et al, 2020 ; Click et al, 2019 , 2020 ; Cooper et al, 2018 ; Eriksson & Safer, 2016 ; Gibson et al, 2020 ; Levy et al, 2021 ; Marshall et al, 2017 ; Park & Safer, 2018 ; Safer & Pearce, 2013 ; Sawning et al, 2017 ; Taylor et al, 2018 ; Underman et al, 2016 ; Vance et al, 2017 ). In some cases, this was linked to “the fact that [the training] was elective and might have attracted a sample of students who were already interested and informed on the topic” (Eriksson & Safer, 2016 , p. 840).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other facilitators were commonly identified at the audience level about which most authors referred to the advantage of students’/residents’ pre-existing awareness, knowledge, positive attitudes, interest, perceived significance, prior professional and/or lived experience that was a foundation for further learning on the topic of transgender health (Berenson et al, 2020 ; Click et al, 2019 , 2020 ; Cooper et al, 2018 ; Eriksson & Safer, 2016 ; Gibson et al, 2020 ; Levy et al, 2021 ; Marshall et al, 2017 ; Park & Safer, 2018 ; Safer & Pearce, 2013 ; Sawning et al, 2017 ; Taylor et al, 2018 ; Underman et al, 2016 ; Vance et al, 2017 ). In some cases, this was linked to “the fact that [the training] was elective and might have attracted a sample of students who were already interested and informed on the topic” (Eriksson & Safer, 2016 , p. 840).…”
Section: Resultsmentioning
confidence: 99%
“…However, such initiatives are often isolated or not structurally embedded in the curriculum, do not always reach all students, and do not always have access to the pedagogical conditions (e.g., experienced and knowledgeable staff, curriculum time and financial and material resources) necessary to optimize teaching and learning about transgender health. Educators also urge for more emphasis on the incorporation of complexity in sessions about transgender health, for instance by exploring identity factors that intersect with transgender identity, such as sexuality, ethnicity/race, class and age in teaching material (Barrett et al, 2021 ; Bi et al, 2020 ; Biro et al, 2021 ; Levy et al, 2021 ; Muntinga et al, 2020 ). And while we found that involvement of transgender perspectives in developing and delivering content was beneficial for student learning and part of necessary advocacy work, some authors warn of overburdening people with lived experiences (including transgender students), in particular when experiential knowledge cannot be properly compensated (Bi et al, 2020 ; Biro et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…healthcare programs ( 28 ). However, despite a positive impact on the students, there are only a limited number of published studies in this area, and more needs to be done to substantiate the intended widespread curricular change ( 27 29 ). With continued efforts in this field, expanded culturally competent interprofessional collaboration could be beneficial to improving healthcare for LGBTQIA+ patients.…”
Section: Discussionmentioning
confidence: 99%
“…These negative attitudes can be associated with lower acceptance, discrimination, and mental health issues, which, in turn, have been found to be related with medical schools dropout [18]. On the contrary, positive attitudes are correlated with higher levels of LGBTQ+ knowledge and confidence among medical students in providing care to LGBTQ+ patients [14,15,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the attitudes of medical students towards LGBTQ+ individuals is crucial for revising an LGBTQ+ inclusive curriculum that prepares students to provide care to LGBTQ + patients and become LGBTQ+-friendly professionals [14,15,[19][20][21]. Since attitudes differ globally, it is important to conduct psychosocially and culturally specific studies to investigate attitudes, and previous research has primarily focused on non-Asian contexts.…”
Section: Introductionmentioning
confidence: 99%